(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
The Going Glocal project, run at University College Roosevelt (Utrecht University) in the years 2013-2014, has the aim of providing students with more knowledge to reflect about issues of global justice in a society shaped by processes of globalisation and cosmopolitanisation, and thus an increased interconnectedness. Fifteen students attended courses on Global Justice and Activism in Mexico and Global Citizenship and went on a fieldtrip to Mexico during the summer. To answer the questions did the students self-other conceptualisation change? two out of the ten interviews conducted between September and January 2014 at UCR are analysed in the light of Social Identity and Social Representation Theory. The participants, who acquired knowledge about Latin American theory and encountered members of the Zapatistas movement, constructed the other and approached the issues of taking responsibility and knowledge from very different perspectives, thus displaying the diversity of the impact this project had on its participants.